(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was included the manufacture of 6 treatments of soft cheese by adding the probiotic of Lactobacillus Plantarum and its metabolic products. as well as, its dead cells after killing them by heat until they curd in121ºfor15minutes. Two concentrations of 5 and 10% have been used for each addition, and comparing these treatments with a control. The results showed that an increase in bacterial numbers in the control treatment and in the number of coliform bacteria, with the appearance of yeasts and molds as the storage period progressed toward 24 days. However, it was noted that in the treatment of cheese containing the probiotic Lactobacillus Plantarum and its metabolites, the bacterial numbers were lower and more stable, such that no clear development was observed in their numbers during a period of 24 d when stored at 7±1oC. It was also recorded that these treatments were free of cold bacteria, coli bacteria, yeasts, and molds. Thus, these results were reflected in the chemical properties of these treatments in terms of pH, total acidity, dissolved nitrogen, and the degree of fatty decomposition. Their values were lower in the fortified treatments compared to the control treatment, which showed a clear deterioration after 10 days of preservation at 7±1 oC.